Periostin-binding DNA aptamer treatment attenuates renal fibrosis under diabetic conditions - Jae Eun Um (Nature Portfolio, 2017)
Abstract Diabetic nephropathy, the major cause of chronic kidney disease, is associated with progressive renal fibrosis. Recently, accumulation of periostin, an extracellular matrix protein, was shown to augment renal fibrosis. Aptamers have higher binding affinities without developing the common side effects of antibodies. Thus, we evaluated the effect of periostin inhibition by an aptamer-based inhibitor on renal fibrosis under diabetic conditions. In vitro, transforming growth factor-β1 (TGF-β1) treatment significantly upregulated periostin, fibronectin, and type I collagen mRNA and protein expressions in inner medullary collecting duct (IMCD) cells. These increases were attenuated significantly in periostin-binding DNA aptamer (PA)-treated IMCD cells exposed to TGF-β1. In vivo, PA treatment attenuated the increased blood urea nitrogen levels in the diabetic mice significantly. Fibronectin and type I collagen mRNA and protein expressions increased significantly in the kidneys of diabetic mice: PA administration abrogated these increases significantly. Immunohistochemistry and Sirius Red staining also revealed that fibronectin expression was significantly higher and tubulointersititial fibrosis was significantly worse in diabetic mice kidneys compared with control mice. These changes were ameliorated by PA treatment. These findings suggested that inhibition of periostin using a DNA aptamer could be a potential therapeutic strategy against renal fibrosis in diabetic nephropathy.